Borehole logging from the Fucino Basin, hole F-4 - Wonik, Thomas; Grelle, Thomas; Hesse, Katja; Zeeden, Christian (Alfred Wegener Institute - Research Unit Potsdam, 2019)
Borehole logging data (gamma ray, magnetic susceptibility) from the the Fucino Basin, hole F-4. Data as in Giaccio et al. (2019), doi:10.1016/j.quascirev.2019.106003
Keywords: borehole logging data; gamma; susceptibility